SHERESHEVSKY-TURNER SYNDROME IN AORTIC SURGERY: AN EXAMPLE OF HYBRID ANEURISM TREATMENT AND DISSECTION OF THORACOABDOMINAL AORTA - E. R. Tchartchan; S. A. Abugov; R. S. Polyakov; E. V. Zaklyazminskaya; V. A. Rumyantseva; V. V. Khovrin; A. A. Skvortsov; M. N. Kabanova; Z. R. Khatchatryan; N. V. Oparina (Российский кардиологический журнал, 2015)
Shereshevsky-Turner syndrome — is chromosome anomaly, the monosomia by X-chromosome (cariotype 45, X0) that has prevalence 1:2000-1:2500 newborn girls. It is well known that these patients very often have cardiovascular pathology. Aortic aneurysm is 100 times more common than in general population. Another significant specifics is the high risk of aortic dissection even with relatively small diameter of aorta, than in average for the dissections. Currently it is common to concern a variety of aortic pathology treatment ways in patients with the syndrome: traditional open-chest interventions, endovascular treatment, hybrid operations. The article provides an example of successful usage of the hybrid method in women 58 years old with Shereshevsky-Turner syndrome, thoracoabdominal aortic aneurysm and dissection of descending thoracal and abdominal aorta parts. The clinical example shows that hybrid method makes it to perform radical intervention on aorta, decreasing traumaticity of operation, mortality and complications rate in postoperation period.